Dioecy and monoecy in the flora of Sri Lanka and their evolutionary correlations to endemism, growth form, fruit type, seed number and flower size - Senarath, W.T.P.S.K. (Bangladesh Journal of Plant Taxonomy, 2008)
The frequency of dioecy and monoecy and the ecological correlates of each sexual system were examined for the flora of Sri Lanka, a tropical continental island. Of the 3,529 species in the total flora, 7.05% are dioecious, 10.25% are monoecious, 1.7% are polygamodioecious, 1.9% are polygamous and 79.1% are hermaphrodites. Study was carried out to test the null hypothesis that the proportionate distribution of dioecious and monoecious taxa in endemism, growth form, fruit type, seed number or flower size was not significantly different from that for the entire flora. Both monoecious and dioecious species in the Sri Lankan flora are significantly associated with the growth form, fruit type, seed number and flower size, whereas only dioecy is associated with endemism. Dioecious species are favored by trees and small flowers, whereas monoecious species are favored by herbs and minute flowers. Both dioecious and monoecious species are, however, associated with fleshy fruits suggesting that animal dispersal of fruits is favored in the Sri Lankan flora. Keywords: Flora, Evolutionary correlations, Dioecy, Monoecy, Sri Lanka DOI: 10.3329/bjpt.v15i1.907 Bangladesh J. Plant Taxon. 15(1): 13-19, 2008 (June)